2009
DOI: 10.5962/bhl.title.51000
|View full text |Cite
|
Sign up to set email alerts
|

Geographically isolated wetlands and intermittent/ephemeral streams in Montana : extent, distribution, and function

Abstract: of EPA Region 8 for their support, and for their commitment to advancing wetland science in the Rocky Mountain West. Several people assisted with the GIS work, wetland mapping, and analysis. Jane Horton, now of Montana Fish, Wildlife and Parks, built the original analytic template. Joey Diehl of the MTNHP Spatial Analysis Lab created several datasets. Meghan Bums, Sloane Gray, Cat Mclntyre and Karen New-Ion of MTNHP all worked on mapping and quality control. Erika Colaiacomo of MTNHP helped with data analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
1
7
0
1
Order By: Relevance
“…perennial streams in the basin (Caruso and Haynes, 2011), which has also been found in a number of other areas (Vance, 2009;Fritz et al, 2013). Our study using the NHD high-resolution data also showed that almost half the reaches in Cement…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…perennial streams in the basin (Caruso and Haynes, 2011), which has also been found in a number of other areas (Vance, 2009;Fritz et al, 2013). Our study using the NHD high-resolution data also showed that almost half the reaches in Cement…”
Section: Discussionsupporting
confidence: 84%
“…In the Southern Rockies Ecoregion perennial streams comprise more than half of total stream length and intermittent streams make up the remainder (Caruso and Haynes, ). Using high‐resolution NHD data, Vance () found that in mountain ecoregions in Montana perennial streams ranged from 35 to 53% of all mapped streams, intermittent reaches accounted for 17 to 26%, and ephemeral streams ranged from 30 to 39%. Caruso and Haynes () showed that in the Upper Colorado River Basin, where Cement Creek is located, >50% of reaches are intermittent first order, and 9% are perennial first order based on the medium‐resolution data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with the range of differences or errors above, the classifications of perennial and intermittent streams are generally considered satisfactory by USGS (Simley, 2007; Vance, 2009), and the 1:100,000 scale data are often used in national and regional‐scale studies (Nadeau and Rains, 2007; Levick et al. , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Son zonas de transición entre los ambientes terrestres y acuáticos y constituyen un vínculo dinámico entre ambos sistemas (Mitsch y Gosselink 2007). A grandes rasgos, pueden subdividirse en dos grupos (Zilli et al 2008, Vance 2009 "conectados" y "aislados".…”
Section: Hidrología De Los Humedalesunclassified